OPTIMIZING EMOTIONAL INTELLIGENCE THROUGH COLLABORATIVE LEARNING IN GRADE III ELEMENTARY SCHOOL STUDENTS - Anita Rosti Azizah; Beti Istanti Suwandayani; Bustanol Arifin (Universitas Majalengka, 2024)
Emotional intelligence is an important ability that every student must have. However, many students still have not mastered emotional intelligence well as a result, students find it difficult to control emotions, and have difficulty establishing communication with peers, so this can have an impact on social interactions and also the teaching and learning process in the classroom. Collaborative learning emerges as one of the effective methods that can be used to overcome these difficulties because this method allows students to practice and develop their emotional skills through active interaction and cooperation with classmates, which can improve emotional intelligence. The purpose of this study is to find out how collaborative learning can contribute to improving students' emotional intelligence. The research method used is qualitative with a descriptive approach, with the 3rd-grade teacher of SDN Dadaprejo 01 as the main informant of the research. Data was collected through observation, interviews and documentation. The results showed that heterogeneous grouping strategies, role assignment, encouraging communication and presentation showed a positive contribution to increasing students' emotional intelligence. Engaging in collaborative learning provides opportunities for students to interact directly with peers, which can improve communication skills, empathy and the ability to control emotions in various social contexts, with this students' emotional intelligence can develop regardless of students' academic success.